Impact of Exchange Rate Regimes and Euro Area Membership on the Economic Growth of the New Member States from Central and Eastern Europe - Todorov, Ivan Krumov; Tanchev, Stoyan; Durova, Kalina; Yurukov, Petar (International Journal of Contemporary Economics and Administrative Sciences, 2021)
The goal of this paper is to study the effects of exchange rate arrangements and euro area (EA) membership on the economic growth of ten new member states (NMS) from Central and Eastern Europe (CEE), which joined the European Union (EU) in 2004 and 2007 – the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, Slovakia, Slovenia, Bulgaria and Romania. Croatia is excluded from the analysis since it became a EU member relatively late - in 2013. A vector autoregression (VAR) of annual data for the period 2007-2017 is employed. The empirical results provide statistical evidence that flexible exchange rates and EA membership favor the economic growth of the NMS from CEE.